Food Environment and Nutritional Status of Children Living in Orphanage Homes in Ogun State, Southwest Nigeria (African Journal of Biomedical Research, 2023)
Children living in orphanage homes world-wide often present with nutritional deficiencies. This can be attributed to lack of proper food environment which encompasses the availability, accessibility and affordability of food. This study examined the food environment and nutritional status of children living in orphanage homes in Ogun State. The study was a descriptive cross-sectional survey that adopted the survey research method with 200 children both males and females aged between 5-11years were randomly selected from 4 Orphanage homes in Ogun State. Among the children surveyed, 3.2%, 10%, 0.5%, 3.5% were normal nutritional status wasted, stunted, underweight, and overweight respectively. There were more girls stunted and wasted than boys, more boys were underweight than girls and more girls were overweight than boys. This study showed that food is affordable, accessible, and available in the orphanage homes and the food environment does not affect the nutritional status of the children living in orphanage homes in Ogun State. In this study, high prevalence of malnutrition was observed among children between 5 to 7 years old. The findings of this study showed that prevalence of malnutrition among children living in orphanage homes in Ogun State is low.